2011
DOI: 10.1007/s00299-011-1175-y
|View full text |Cite
|
Sign up to set email alerts
|

Expressed sequence-tag analysis of ovaries of Brachiaria brizantha reveals genes associated with the early steps of embryo sac differentiation of apomictic plants

Abstract: In apomixis, asexual mode of plant reproduction through seeds, an unreduced megagametophyte is formed due to circumvented or altered meiosis. The embryo develops autonomously from the unreduced egg cell, independently of fertilization. Brachiaria is a genus of tropical forage grasses that reproduces sexually or by apomixis. A limited number of studies have reported the sequencing of apomixis-related genes and a few Brachiaria sequences have been deposited at genebank databases. This work shows sequencing and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 54 publications
(61 reference statements)
0
24
0
Order By: Relevance
“…This approach is complicated by the nature of asexual reproduction that prevents the generation of isogenic lines that differ solely with regard to reproductive mode. Nevertheless, transcriptome comparisons between apomictic and closely related sexual individuals from reproductive tissues at different developmental stages have uncovered pathways potentially central to apomixis including protein degradation, transcription, stress response, and cell-to-cell signaling (Albertini et al 2005;Laspina et al 2008;Sharbel et al 2010;Silveira et al 2012;Okada et al 2013).…”
Section: Differentially Expressed Genes Associated With Apomixismentioning
confidence: 99%
See 2 more Smart Citations
“…This approach is complicated by the nature of asexual reproduction that prevents the generation of isogenic lines that differ solely with regard to reproductive mode. Nevertheless, transcriptome comparisons between apomictic and closely related sexual individuals from reproductive tissues at different developmental stages have uncovered pathways potentially central to apomixis including protein degradation, transcription, stress response, and cell-to-cell signaling (Albertini et al 2005;Laspina et al 2008;Sharbel et al 2010;Silveira et al 2012;Okada et al 2013).…”
Section: Differentially Expressed Genes Associated With Apomixismentioning
confidence: 99%
“…In the aposporous grass Brachiaria brizantha, low-depth expressed sequence tag (EST) libraries made from ovaries of sexual and apomictic individuals revealed ESTs that show similarity to genes with known involvement in female embryo sac development (Silveira et al 2012). Further characterization of some of these ESTs identified genes that are expressed in the region where aposporous initial cells appear.…”
Section: Differentially Expressed Genes Associated With Apomixismentioning
confidence: 99%
See 1 more Smart Citation
“…Different experimental techniques such as map-based cloning approaches, differential display, subtractive hybridisation, and mimicking apomixis in sexual model plants have been used to investigate the genetic factors regulating apomixis and have led to the identification of many candidate genes28. These genes participate in many processes potentially central to apomixis, including protein degradation, transcription, stress response, and cell-to-cell signalling1427293031. Recent research has highlighted the influence of plant hormones (such as auxin and cytokinin323334) and epigenetic regulation353637 on asexual embryogenesis, suggesting their involvement in apomixis induction and regulation.…”
mentioning
confidence: 99%
“…The role of the synergid cells remains an open question in species whose embryo and endosperm development is independent of any contribution from pollen, but there has been some progress recently in, for example, Brachiaria brizantha, where synergids were found to be involved in autonomous embryo development (Alves et al, 2007;Silveira et al, 2012). In this species, molecular analysis of the temporal and spatial expression of certain cDNA sequences by in situ hybridization in ovaries of apomictic and sexual plants indicated that synergids may play a crucial role not only at the moment of fertilization but also in the autonomous development of an unreduced egg cell.…”
Section: Discussionmentioning
confidence: 99%